A Time-Domain CMOS Oscillator-Based Thermostat with Digital Set-Point Programming - Shih-Hao Lin; Chun-Chi Chen (Sensors, 2013)
This paper presents a time-domain CMOS oscillator-based thermostat with digital set-point programming [without a digital-to-analog converter (DAC) or external resistor] to achieve on-chip thermal management of modern VLSI systems. A time-domain delay-line-based thermostat with multiplexers (MUXs) was used to substantially reduce the power consumption and chip size, and can benefit from the performance enhancement due to the scaling down of fabrication processes. For further cost reduction and accuracy enhancement, this paper proposes a thermostat using two oscillators that are suitable for time-domain curvature compensation instead of longer linear delay lines. The final time comparison was achieved using a time comparator with a built-in custom hysteresis to generate the corresponding temperature alarm and control. The chip size of the circuit was reduced to 0.12 mm2 in a 0.35-mm TSMC CMOS process. The thermostat operates from 0 to 90 °C, and achieved a fine resolution better than 0.05 °C and an improved inaccuracy of ± 0.6 °C after two-point calibration for eight packaged chips. The power consumption was 30 µW at a sample rate of 10 samples/s.